A Comparison of Peak Intensity Periods across Male Field Hockey Competitive Standards - Eoin Cunniffe; Adam Grainger; Walter McConnell; Ulrik McCarthy Persson; Eamonn Delahunt; Colin Boreham; Catherine Blake (MDPI AG, 2021)
This investigation aimed to compare the international level peak intensity period of male field hockey players to those experienced during professional and amateur club hockey match play. Twenty-seven players from an international squad were monitored for all activity relating to field hockey over three seasons. The peak intensity period, of 3 min duration, was extracted from match play files for international and club matches. Club matches were categorised by league standard-professional vs. amateur. The output for the peak intensity period, within positions, was compared using linear mixed models (LMMs) and post hoc pairwise comparisons. Significance levels were set as p < 0.05 and Cohen's d was utilised for effect sizes. Competition level had a main effect on relative total distance (p < 0.05) and significant interaction effects were found between competition level and position (p < 0.05). Midfielders competing in amateur leagues and international match play completed less relative total distance than those who compete in professional leagues (−47.88 m/min, p < 0.05), (−46.06 m/min, p < 0.05) with large effect sizes reported. No other position displayed significant differences for peak periods. Match play in professional leagues provide opportunities for midfielders to experience peak intensity periods of a greater magnitude than international match play.